XRF data from stomach oil deposit WMM7, Dronning Maud Land - McClymont, Erin L; Bentley, Michael J; Hodgson, Dominic A; Spencer-Jones, Charlotte L; Wardley, Thomas; West, Martin; Croudace, Ian W; Berg, Sonja; Gröcke, Darren R; Kuhn, Gerhard; Jamieson, Stewart; Sime, Louise C; et al. (In: McClymont, EL et al. (2021): Age model, XRF data, fatty acid distributions and stable isotope analysis for stomach oil deposit WMM7, Dronning Maud Land [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.939211, 2021)
XRF analysis of stomach-oil deposit WMM7.
Keywords: Antarctica; Last Glacial; mumiyo; Sea ice; XRF